Sistem Pendukung Keputusan Pemilihan Tempat Kost Mahasiswa Menggunakan Metode Saw (Simple Additive Weighting) - Muhammad Daffa Sumarto; Winny Purbaratri; Dwi Atmodjo Wismono Prapto; M. Isnin Faried (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2023)
Boarding homes are very crucial for students who live far from home, especially for those who go to Perbanas Institute. Choosing a boarding home has frequently been done without a defined procedure, which has made it hard for students to identify alternatives that fit their needs and budget. This study creates a web-based decision support system (DSS) for choosing boarding homes based on the Simple Additive Weighting (SAW) technique. This technique gives each criterion price, distance to campus, facilities, security, and room size weights. These weights are then used to find the best option from the 10 available by normalizing and ranking them. Surveys, observations, and reading books were used to gather research data. The weights were then set depending on what the students wanted. The results of the calculations reveal that